Improving ESP Vietnamese learners’ EFL speaking fluency and vocabulary with DMGA scaffolding: a modular approach - Nhi, Nguyen Tran Uyen; AlSaqqaf, Asmaa (Institute of Advanced Engineering and Science, 2025)
Teaching English as a foreign language (EFL) speaking in an English for specific purposes (ESP) classroom can be challenging as many Vietnamese students find it difficult to master this language skill. To address this issue, scaffolding is believed to be beneficial in language learning programs. This paper aims to investigate the effectiveness of the Diagnosing, Modeling, Sharing, Guiding, and Applying (DMGA) scaffolding-based module on improving the speaking skills of ESP Vietnamese learners at a public university in Vietnam in terms of fluency and vocabulary use. The study employed a quantitative method with an experimental design. The participants were 25 ESP undergraduates. The English-speaking performance test (ESPT), which served as a pretest and posttest, revealed that most posttest indicators improved from pretest values, though significance and size effects varied. Students performed significantly better in both breakdown fluency and speech rate, but there was no progress in repair fluency. While there was no statistically significant improvement in all vocabulary metrics (type-token ratios (TTR), voice-to-text ratio (VOCD), English vocabulary profile (EVP)), the students did achieve higher mean scores on the measures of vocabulary used in the post-test. Based on the findings, the DMGA scaffolding model should be applied to teach speaking skills in ESP settings within an EFL context to benefit both teachers and learners.